Considerations for the use of immunosuppression for the management of pemphigus during the COVID-19 pandemic with a focus on rituximab: Case reports from a single center experience in Australia - Koszegi, Ben; Stone, Corey; Murrell, Dedee F. (Frontiers in Medicine, 2023)
Pemphigus is a rare group of autoimmune mucocutaneous blistering conditions for which the mainstay of treatment is immunosuppression. This is usually achieved with high dose corticosteroids as well as steroid sparing agents. Rituximab is now recommended as a first line treatment for moderate to severe pemphigus vulgaris, the commonest form of pemphigus, alongside corticosteroids. During the early stages of the COVID-19 pandemic the use of rituximab was reduced in our department due to its long term irreversible B-cell suppression. During the COVID-19 pandemic careful pharmacological selection was undertaken for our pemphigus patients to balance the risks of immunosuppression. To demonstrate this, we report three pemphigus patients who required treatment for COVID-19 and assessment throughout the pandemic. To date there has been limited published data regarding the clinical outcomes of pemphigus patients who have developed COVID-19 infections following rituximab infusions, especially in those patients who have received COVID-19 vaccinations. Following careful personalized consideration, all three pemphigus patients presented received rituximab infusions since the start of the COVID-19 pandemic. These patients had also received COVID-19 vaccinations prior to becoming infected with COVID-19. Each patient had a mild COVID-19 infection after receiving rituximab. We advocate for all pemphigus patients to have a full course of COVID-19 vaccinations. Antibody response to COVID-19 vaccinations should ideally be confirmed by measuring pemphigus patient’s SARS-CoV-2 antibodies prior to receiving rituximab.